2022
DOI: 10.1155/2022/5783867
|View full text |Cite
|
Sign up to set email alerts
|

Duchesnea indica Extract Ameliorates LPS-Induced Septic Shock in Mice

Abstract: Objective. Duchesnea indica has been reported for its anti-inflammatory properties. However, its efficacy in sepsis has yet to be reported. In this study, we studied the ability of Duchesnea indica extract (DIE) to rescue mice from septic shock and sepsis. Methods. In vitro studies included the measurement of secreted nitric oxide, cell viability, gene and protein expression via real-time polymerase chain reaction and western blot, and confocal microscopy in RAW 264.7 cells. In vivo studies include a model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…This compound has been the secondary metabolite mostly identified in alcoholic extracts of Potentilla indica. In 2022, Lee et al [51] demonstrated that the oral administration of ethanolic extract of the Potentilla indica (100 and 300 mg/kg) in which ellagic acid was identified by UPLC as the major component, ameliorates LPS-induced septic shock in mice and decreases the levels of inflammatory markers in the serum of mice in a chronic sepsis model by suppressing NF-κB translocation to the nucleus of lung cells in a dose-dependent manner. Similarly, in 2008, Zhao and colleagues [34] demonstrated that ethanolic extract of Potentilla indica (whole plant) displayed anti-inflammatory activity in an inflammatory cell model by addition of lipopolysaccharide (LPS, 10 ng/mL) in the RAW264.7 cell line in the presence of 10, 5, and 1 μg/mL concentrations of the extract for 24 h, blocking NF-κB activation.…”
Section: Anti-inflammatory Effect Of Potentilla Indicamentioning
confidence: 99%
“…This compound has been the secondary metabolite mostly identified in alcoholic extracts of Potentilla indica. In 2022, Lee et al [51] demonstrated that the oral administration of ethanolic extract of the Potentilla indica (100 and 300 mg/kg) in which ellagic acid was identified by UPLC as the major component, ameliorates LPS-induced septic shock in mice and decreases the levels of inflammatory markers in the serum of mice in a chronic sepsis model by suppressing NF-κB translocation to the nucleus of lung cells in a dose-dependent manner. Similarly, in 2008, Zhao and colleagues [34] demonstrated that ethanolic extract of Potentilla indica (whole plant) displayed anti-inflammatory activity in an inflammatory cell model by addition of lipopolysaccharide (LPS, 10 ng/mL) in the RAW264.7 cell line in the presence of 10, 5, and 1 μg/mL concentrations of the extract for 24 h, blocking NF-κB activation.…”
Section: Anti-inflammatory Effect Of Potentilla Indicamentioning
confidence: 99%
“…Variations in the extracted DI phytochemicals based on the solvents used and differences in antibacterial properties were previously reported [26]. Moreover, other studies have reported the application of the ethanol extract of DI as a treatment for sepsis and the water extract of DI as a medicinal cosmetic against skin pathogens such as S. aureus and S. epidermidis [39,40]. Overall, the synthesized AgNPs exhibited better antibacterial activity than AgNO3, but their effect on bacteria varied from that of the DI extract.…”
Section: Antibacterial Activity Of Biosynthesized Agnpsmentioning
confidence: 99%